64.0k views
0 votes
-4(3s) + 2(-t)

if s = 1/2 and t = -3, what would the answer be?

-4(3s) + 2(-t) if s = 1/2 and t = -3, what would the answer be?-example-1

2 Answers

2 votes

Answer:

The expression would be = to 0.

Explanation:

Starting with -4(3s) + 2(-t), substitute (1/2) for s and (-3) for t:

-4(3/2) + 2(+3)

This gives us:

-12/2 + 6 = 0

User Nick Jones
by
3.8k points
4 votes

Answer:

-12

Explanation:

3 times 1/2 is 1 1/2. 1 1/2 times -4 is -6. Then, -3 times 2 equals to -6. lastly -6 plus -6 equals to -12

User Wanderfalke
by
5.0k points